Oil Extraction and Production of A Biodiesel Using Vegetable Oil Derived From Algae (Scenedesmus dimorphus) - Indro Prastowo (JURNAL BIOEDUKATIKA, 2013)
Biodiesel is a biofuel which is projected to substitute diesel oil.Keyword: Scenedesmus dimosphus, biodiesel, sand, n-hexane